Above- and Belowground Plant Functional Composition Show Similar Changes During Temperate Forest Swamp Succession - Hu, Yu-Kun; Pan, Xu; Liu, Xu-Yan; Fu, Zhi-Xi; Zhang, Man-Yin (Frontiers in Plant Science, 2021)
Plant functional composition, defined by both community-weighted mean (CWM) traits and functional diversity, can provide insights into plant ecological strategies and community assembly. However, our understanding of plant functional composition during succession is largely based on aboveground traits. Here we investigated community-level traits and functional diversity for six pairs of analogous leaf and fine root traits of understory plants in a temperate forest swamp during succession with a decrease in soil pH and nutrient availability. CWMs of traits related to resource acquisition (including specific leaf area, specific root length, leaf N, leaf P, root N, and root P) decreased with succession, whereas those related to resource conservation (leaf dry matter content, root dry matter content, leaf tissue density, leaf C, and root C) increased along the forest swamp successional gradient. Multi-trait functional dispersion (FDis) of both leaf and fine root traits tended to decrease along the successional gradient, but functional richness and evenness were highest at the middle successional stage. Moreover, FDis of individual plant traits except N showed the same pattern as multi-trait FDis. Soil pH and nutrient availability were the main drivers of successional changes in both CWM traits and FDis. The changes of community-level traits along succession indicated a shift from acquisitive to conservative strategy of understory plants during forest swamp succession. Similar trends in leaf and fine root functional diversity along succession may indicate above- and belowground functional diversity are coordinated during the processes of plant community assembly. These findings of linkages between above- and belowground plant functional composition have important implications for plant community dynamics and assembly rules.